Jk-integral applied to mixed-mode fatigue crack propagation and life prediction in metal welding interface. (15th April 2023) - Zhang, Zhenjie; Liu, Ran; Zhang, Kaining; Sun, Dexin; Zhang, Yanming; Hou, Junling; Li, Maoqing; Li, Mengjie; Li, Qun
Highlights: A new fatigue model of metal welding interface is proposed based on Jk -integral. DIC method is investigated to measure the Jk -integral at the interface crack tip. The proposed model includes the prediction of crack propagation path and life. The model can clearly describe the two-stage process under mixed-mode loading. Abstract: In this paper, an innovative fatigue crack propagation model of metal welding interface is investigated based on the concept of Jk -integral ( k  = 1, 2) in elastic–plastic material, including the prediction of crack propagation path and life. In order to validate the effectiveness of the present fatigue model, the experiments of mixed-mode interface fatigue cracks are carried out on compact tensile shear specimens of N36 zirconium alloy using DIC methods. The results demonstrate that the fatigue crack only propagates along the interface under mode I loading where the relationship between the crack growth rate da / dN and Δ J 1 (the J 1 -integral range per loading cycle) is logarithmic linear. As for mode I/II mixed-mode loading, interface cracks start to propagate along the interface when J 1 reaches J int-C (the interface fracture toughness). When J total (the vector sum of J 1 and J 2 ) reaches J sub-C (the substrate fracture toughness), the crack deflects to the substrate in the J total direction. In this case, da / dN shows a two-stage logarithmic linear relation with Δ J total (the J total -integral range per loading cycle) under mixed-mode loading, and the critical J total at the beginning of crack deflection is approximately matching the specific value. The theoretical deflection angle (i.e. the J total direction) calculated from the corresponding J 1 and J 2 at the beginning of crack deflection is well consistent with the actual deflection angle observed in experiments. Moreover, the model can clearly describe the two-stage process from the crack propagation along the interface to the crack deflection to the substrate under mixed-mode loading. It is concluded that the proposed fatigue model based on Jk -integral can accurately predict the fatigue crack propagation path and lifetime of metal welding interface.